RMS Lg as a Yield Estimator in Eurasia. Part 1 - Israelsson, Hans (1992)
This report has been divided into two parts. The first part is devoted entirely to a description of, and research performed on, the hand digitized waveforms of Soviet regional data that were obtained by Dr Alan Ryall of DARPA and Sgt Mike Berry of AFTAC as part of the bilateral Nuclear Testing Talks between the US and the former USSR. Digitized by ENSCO Inc at Indian Harbour Beach, FL, the data were subsequently compiled by Dr Herron and her staff at AFTAC and are now available at the Center for Seismic Studies. The first paper of Part 1 is a description of the data. This is followed by two papers that analyzed the RMS Lg magnitudes at Novaya Zemlya and Semipalatinsk, respectively. The Semipalatinsk report also compares the RMS Lg measurements and Bocharov yields as well as exploring the effects of depth on the magnitude measurement. The fourth paper combines the data from the two test sites with data from underground nuclear explosions elsewhere in the former Soviet Union in a decomposition of the RMS Lg measurement into source, path, and station terms. The last paper examines the RMS Lg measurement as a function of frequency in order to explain the variability of the mb (Lg) - yield scale among stations. See also Part 2, ADA256691.